2021
DOI: 10.1007/s00204-021-02992-7
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-induced inflammation and fibrosis in ex vivo murine precision-cut liver slices and effects of nanoparticle exposure conditions

Abstract: Chronic exposure and accumulation of persistent nanomaterials by cells have led to safety concerns on potential long-term effects induced by nanoparticles, including chronic inflammation and fibrosis. With this in mind, we used murine precision-cut liver tissue slices to test potential induction of inflammation and onset of fibrosis upon 72 h exposure to different nanomaterials (0–200 µg/ml). Tissue slices were chosen as an advanced ex vivo 3D model to better resemble the complexity of the in vivo tissue envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 83 publications
1
12
0
Order By: Relevance
“…Dragoni et al confirmed the internalization and active uptake of gold particles in all three cell types [64]. Bartucci et al, on the other hand, demonstrated the nanosafety after long-term (72 h) exposure to nanoparticles [56]. These experimental set-ups demonstrate the applicability of PCLS cultures not only for disease modelling but clinical applications as well.…”
Section: Liver Diseasementioning
confidence: 83%
See 2 more Smart Citations
“…Dragoni et al confirmed the internalization and active uptake of gold particles in all three cell types [64]. Bartucci et al, on the other hand, demonstrated the nanosafety after long-term (72 h) exposure to nanoparticles [56]. These experimental set-ups demonstrate the applicability of PCLS cultures not only for disease modelling but clinical applications as well.…”
Section: Liver Diseasementioning
confidence: 83%
“…Next to H&E stainings, mostly a Picrosirius Red (PiSR) staining or to a lesser extent, a DAB (3,3 -Diaminobenzidine) staining are performed. A few papers also make use of cryosections for immunofluorescence (IF) [56,57] or Oil Red O (ORO, lipid accumulation) stainings [22,58] and some studies do not even section the slices for the ORO staining [59,60]. Overall, only a few PCLS research papers (<10% of investigated papers) show immunostainings, with HSC markers (e.g., αSMA, Collagen) and Ki67 being the mostly used antigens.…”
Section: Protein Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, hepatocyte uptake of PEG-GNPs provoked intracellular multivesicular endosome (MVE) formation and exosome secretion both of which have been reported as natural Trojan horses to trigger induction, amplification, and/or modulation of immune responses in immune signaling. , We have shown that PEG-GNP treatment induced significant upregulation of stress response-related and proinflammation-associated gene expressions; , thus, the elevation of related proteins could occur. In addition, the elevation of proinflammatory cytokines would recruit blood inflammatory cells (leukocytes, neutrophils, and lymphocytes) to the hepatic inflammatory sites, thereafter elevating the contents of a protein, lipid, and nucleic acid. Further, the significant upregulation of lipogenesis-related gene expression in the liver of PEG-GNP treated mice, such as fatty acid synthase ( Fas ) and stearoyl coenzyme A desaturase 1 ( Scd1 ), was observed in our previous research, which would also play an important role in the variation of lipid contents.…”
Section: Discussionmentioning
confidence: 99%
“…Ag is known to have a sharp and strong plasmon resonance peak [4], showing high toxicity in cancer cells [5][6][7], extensively demonstrated in vitro [8] as well as antibacterial and antimycotic features [9,10]. However, the application of Ag NPs in clinical trials is often hindered by the activation of the inflammatory response [11]; in general, this occurs because the foreign material is recognized as an antigen [12]. Ideally, the NPs should not trigger the immune response in living organisms, when they are used as vectors or therapeutic agents [13].…”
Section: Introductionmentioning
confidence: 99%